Implementation of Problem Based Learning (PBL) Model to Improve SMP Students' Concepts Mastery in Additive Materials and its Correlation with Surat Al Baqarah Verse 168 - Fathoni, Ahmad; Muhtadin, Khoirul (Yayasan Pendidikan Islam Daarut Thufulah, 2024)
The aim of this research is to describe the implementation of learning, describe the increase in Santri's mastery of concepts, and describe the Santri's response after applying the Problem Based Learning learning model to the additive sub-material. A pre-experimental design with One Group Pretest- Posttest Design is used in this type of research. The research subjects used were students from a private junior high school in Trenggalek. This research uses several instruments in the form of learning implementation observation sheets, test sheets, and questionnaires which are then analyzed using quantitative descriptive. The research results show that the implementation of learning achieved very good criteria with mode 4. Normality test, paired t-test, N-Gain were used in research data analysis. The standard test results obtained a significant value of 0.122, which means the data is normally distributed. The paired t-test produces a Sig value. amounting to 0.000 < 0.05, which means there is a significant difference after being given treatment in the form of the Problem Based Learning Model. The increase in students' mastery of concepts can also be seen from the N-Gain results with an average score of 0.87 (high). The students gave a positive response to the application of this learning model by obtaining an average score of 93.81% and the criteria were very high. These results show that Santri's mastery of concepts can increase after implementing the Problem Based Learning Model.